Phases of Human Creation from the Scientific Interpretation Perspective of the Ministry of Religion of the Republic of Indonesia - Kemal Bagja; Usman, Muhamad Hafidz; Abun Nasheer, Rega; Fathurabani, Ali; Baasil Wafdulloh, Muhammad (Institut Agama Islam Persis Bandung, 2024)
This article discusses the creation or origins of humans as stated in Q.S Ali-Imran: 59, Q.S. Al-Mu'minun: 12-14. This study uses a qualitative comparative study method with a literature review approach. The data source is the book